PENGARUH STRES KERJA, LINGKUNGAN KERJA, BEBAN KERJA DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU PAI DI SMA BANTEN - Ali Nurdin; Samudi, Samudi (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
Teacher performance is the main and very urgent factor that enables the realization of educational and learning goals in the school environment. The realization of teacher performance is due to many factors, including: work stress situations, work environment, workload and interpersonal communication. Therefore, many of these matters require special attention from all parties, so that teachers work in harmony with their work. This research aims to examine and analyze the influence of work stress, work environment, workload and interpersonal communication on the performance of Islamic religious education teachers at high schools in Banten. In conducting research, researchers used an ex post facto type of quantitative approach. The research sample was 64 Islamic religious education teachers at private high schools in Pandeglang Banten, with a random sampling method. In obtaining research data, observation, questionnaires and documents were used. Data analysis was carried out in stages, including: data description, validation testing, reliability testing, analysis requirements testing, as well as simultaneous and partial analysis tests. The research results found: work stress on teacher performance has a positive and significant influence. The work environment on teacher performance has a positive and significant influence. Workload on teacher performance has a positive and significant influence. Interpersonal communication on teacher performance has a positive and significant influence. Likewise, work stress, work environment, workload and interpersonal communication have a positive and significant influence on teacher performance. This means that the lower the work stress and workload, the higher the performance of the Islamic religious education teacher. At the same time, as the work environment and interpersonal communication improve, the performance of Islamic religious education teachers will also increase.